Oral Lesions in the Bit Area in Finnish Trotters After a Race: Lesion Evaluation, Scoring, and Occurrence - Tuomola, Kati; Mäki-Kihniä, Nina; Kujala-Wirth, Minna; Mykkänen, Anna; Valros, Anna (Frontiers in Veterinary Science, 2019)
Oral mucosal lesions in the bit area are common in horses, but not comprehensively studied in harness racing horses. This study describes the type and occurrence of oral mucosal lesions in the area affected by the bit, hereafter called the bit area, in trotters after a race. Based on our results, we suggest a system for scoring lesions according to size, type (bruise or wound), age, and depth (superficial or deep). The data was collected during a welfare program for trotters, conducted by The Finnish Trotting and Breeding Association (Suomen Hippos ry). The rostral part of the mouth of 261 horses (151 Standardbreds, 78 Finnhorses and 32 ponies) was examined after a race in a systematic manner, using a bright light source without sedation or a mouth gag. The lip commissures (outside and inside), bars of the mandible, buccal area near the second upper premolar teeth, tongue, and hard palate were visually examined; bars of the mandible were also palpated. Points were assigned to every lesion and then added together, such that each horse got an acute lesion score. Based on the score, the horses were divided into four groups (A—D) as follows: Group A, no lesions; B, mild lesions; C, moderate lesions; D, severe lesions. Of all the horses examined, 84% (219/261) had acute mucosal lesions in the bit area. In total, 21% (55/261) had mild lesions, 43% (113/261) had moderate lesions, and 20% (51/261) had severe lesions. Visible bleeding outside the mouth was observed in 2% (6/261) of the horses. Further, 5% of the horses (13/261) had blood on the bit when it was removed from the mouth, even though no blood was visible outside the mouth. In conclusion, mucosal lesions in the bit area were common in the Finnish trotters examined. Moreover, the absence of blood outside the mouth does not rule out serious mucosal injuries inside the mouth. The scoring system presented can be used for evaluating the severity of oral lesions in different equestrian disciplines and populations to allow for comparable data across studies.